PENGARUH NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP RETURN ON ASSET (STUDI KASUS DI PT BANK BRISYARIAH) - Nur'aeni Nur'aeni; Valia Zadtyva (Universitas Ma'soem, 2019)
This study aims to determine the effect of NPF, FDR and BOPO on ROA both partially and simultaneously at the 2014-2018 BRISyariah Bank. This type of research is associative quantitative with the type of data is secondary data and uses data collection techniques in the form of documentation and literature studies. Population in this study is all financial statements of the Bank of BRISyariah and the sample used is a saturated sample of quarterly financial statements of the Bank of BRISyariah for the period 2014-2018 . Data analysis and hypothesis test design used are multiple correlation analysis, multiple regression analysis, coefficient of determination analysis, t-test and F-test. In data processing, the application uses Statistical Software and Service Solution (SPSS) version 23.The results of this study indicate that there is no significant effect between NPF on ROA, there is a negative and significant influence between FDR on ROA, there is a negative and significant effect between BOPO on ROA, and simultaneously there is a positive and significant effect between NPF, FDR and BOPO on ROA in BRISyariah Bank.